Correlation Between Coagulation Index and Hormone Levels in Patients with ACTH-Independent Cushing's Syndrome - Li, Yanan; Zhao, Xin; Liu, Yi; Zhang, Yushi (Hormone and Metabolic Research, 2025)
The aim of the study was to explore the relationship between hormone levels and coagulation indicators in patients with Cushing’s syndrome, providing insights into disease progression and treatment. We recruited 640 patients diagnosed with ACTH-independent Cushing’s syndrome with adrenocortical tumors, conducting comprehensive physical and laboratory examinations, and analyzing data using logistic regression models. We found that compound F at 8 AM (F8AM) and ACTH had better correlation with coagulation characteristics. We revealed negative association between F8AM levels and PLT or APTT, while ACTH exhibited opposite trends. With F8AM increasing, Fbg declined significantly, while ACTH had the opposite association. In patients with Cushing’s syndrome, chronic cortisol elevations may lead to consumptive coagulopathy, characterized by decreased PLT and Fbg levels, apart from the hypercoagulable state implied by decreased APTT.
Keywords: ACTH-independent Cushing’s syndrome; coagulation; consumptive coagulopathy